Forecasting Model of Shrinkage in Circular Knitted Fabric Using Decision Tree Analysis - Trinh, Thi Kim Hue; Phan, Thanh Nhan; Le, Song Thanh Quynh (Engineering Science Letter, 2025)
Controlling and ensuring product quality are significant in any production department, especially in the textile and clothing industry. Ensuring fabric shrinkage meets customer requirements constitutes a critical factor in evaluating product quality in the knitted fabric production process. However, fabric shrinkage depends on the order‘s specifications, such as loop length, fabric weight, material composition, longitudinal density, and transverse density. This complexity makes it challenging to control and ensure the fabric quality according to customer requirements. This study will describe the characteristics of each specification factor and explore its influence on fabric shrinkage. Finally, data mining techniques develop a forecasting model based on input parameters. The prediction model results will support production managers in estimating and promptly adjusting process parameters to achieve the expected quality levels.